Measurement of total and differential cross sections of neutrino and antineutrino coherent π ± production on carbon - Mislivec A. (2018)
Neutrino induced coherent charged pion production on nuclei, ν¯μA → μ π∓A, is a rare inelastic interaction in which the four-momentum squared transferred to the nucleus is nearly zero, leaving it intact. We identify such events in the scintillator of MINERvA by reconstructing jtj from the final state pion and muon momenta and by removing events with evidence of energetic nuclear recoil or production of other final state particles. We measure the total neutrino and antineutrino cross sections as a function of neutrino energy between 2 and 20 GeV and measure flux integrated differential cross sections as a function of Q2, Eπ, and θπ. The Q2 dependence and equality of the neutrino and antineutrino cross sections at finite Q2 provide a confirmation of Adler’s partial conservation of axial current hypothesis.